ANALISIS DAN PERANCANGAN SISTEM INFORMASI AKADEMIK PADA PG-TK HARUN AR-RASYID BANDUNG - Permatasari, Deasy; Suatkab, Amran (JURNAL GAUNG INFORMATIKA, 2012)
PG-TK Harun Ar-Rasyid is one of the institutions of information systems and data processing operations still use a manual, all the recording was done in a large bookand sheet files. Specifically Academic Information Systems that are running at the moment are still common errors from student data management, data processingdivision, class assessments, and creating reports. The method used is Watterfall sistem development. The method of approach used is a structured system, and tools of analysis is Flowmap, DFD (Data Flow Diagram), and Data Dictionary. With the construction of a computerized system is expected academic information academic activities on PG-TK Harun Ar-Rasyid can produce better work and maximum using a centralized data storage to facilitate the management of information systems academic better